From Tradition to Modernity: Unravelling the Transition of Indigenous Practices in Northeast India - Thomas, Ngaopunii Trichao; Maske, Sudhir (International Journal of Psychosocial Rehabilitation, 2020)
This paper examines the transition from traditional practices to modernity among indigenous communities in Northeast India, with a focus on the Nagas, Mizos, Apatani, and other ethnic groups. The research adopts a mixed-methods approach, combining ethnographic research, focus groups, interviews, questionnaires, and dataset analysis to explore the intricate relationship between these communities and their local environments, specifically within the realms of agriculture. Key findings of the study include the resilience of indigenous knowledge systems in the face of ecological, sociocultural, and economic changes, highlighting how traditional agricultural techniques and natural resource management contribute to sustainability, climate resilience, and biodiversity conservation. The research also examines how modernization influences cultural identity, agricultural methodology, and community development, emphasizing the need for culturally sensitive policies that facilitate a balance between tradition and progress. Through case studies, the study demonstrates the adaptability of communities like the Apatanis, Mizos and Nagas in maintaining their cultural identities and ecological knowledge amidst modernity’s impact. However, the consequences of these transitions, such as ethnic unrest, governance challenges, and disparities in social indicators, are also acknowledged, underlining the need for targeted interventions. The paper’s implications suggest the importance of understanding the multifaceted effects of globalization, urbanization, and modernization on indigenous healthcare, diet, and overall lifestyles. Practical recommendations for sustainable development strategies that respect traditional wisdom while embracing modern advancements are offered. Overall, this work provides essential insights for policymakers aiming to promote sustained well-being, cultural vitality, and resilience in indigenous communities.